Desenvolvimento de embalagem sustentável em papelão ondulado para porcelana de mesa - Adimari, Indra Marianna (2011)
This project objective's is develop sustainable packages which follow the ecodesign pattern, produced with conrrugated cardboard for Germer Porcelanas Finas S.A company. Will be explained subjects like the matter of the way that package acts in logistics economy sector, helping out in the marketing process of a brand and about the fact that the number of companies whose care about environmental responsibility and likewise acts in this way, is increasing. The process of developing this package will be divided in 4 steps, describing all of them from planning to final results, further about ecological stamp creation and an informative folder which tells about sustainable attitudes performed by Germer.